The effect of matrices and bacterial type on uncertainty of microbiological testing - Yotinnl, Kijtisak (Bulletin of Applied Sciences, 2022)
A complete test report shall include the results of the test, along with the uncertainty of the test result. The uncertainty of the test shows the quality of the test results. The estimation of the uncertainty of the microbiological testing are “Top-down approach” that using the standard deviation of reproducibility. The standard ISO/TS 19036:2006/Amd.1:2009(E) mentions various factors that affect the uncertainty of microbiological testing. The data from accredited laboratory according to ISO/IEC 17025 shows that the matrices of the sample affect the uncertainty of the microbiological testing. The uncertainty of microbiological testing from homogeneous sample is smaller than the inhomogeneous sample. In addition, the types of bacteria do not affect on the uncertainty of microbiological testing.